Cover Image. Issue 1 (11th June 2020) - Schulz, David J.; Zornik, Erik
Abstract : The cover image is based on the Editorial Central Pattern Generators Reveal Neuronal Circuit Dynamics Across Many Time scales by David J. Schulz and Erik Zornik, DOI: 10.1002/dneu.22750 . The image shows a representative CPG circuit surrounded by drawings of the species that are evoked as models in the contributions to this special issue. Image by David Schulz (created with Biorender.com).